Export cutoff productivity, uncertainty and duration of waiting for exporting - Lianjie Duan (Economics: The Open-Access, Open-Assessment Journal, 2023)
Using China's transaction-level trade data and firm-level production data during 2000-2006, this study first estimates the duration of Chinese industrial enterprises' waiting for exporting. The results show that the average duration of waiting for exporting is 4.7 years and the median is 5 years. Besides, the hazard rate of export entry has the prominent positive duration dependence. Then, this study uses Cox proportional hazard model to analyse the impact of export cutoff productivity on the duration of waiting for exporting. The result indicates that the rise in the productivity threshold will significantly prolong the duration of waiting for exporting, and this conclusion is supported by a variety of robustness tests. In addition, the estimation result of hazard ratio shows that every 1% increase in productivity threshold will lead to a 0.1261% decrease in hazard rate of enterprises' export entry. Moreover, the heterogeneity test indicates that the effect of export cutoff productivity on duration of enterprises' waiting for exporting has the significant ownership and industry heterogeneity, but does not have the destination heterogeneity. Further, this study finds that China's accession to the World Trade Organisation helps to weaken the threshold effect of export cutoff productivity on the duration of Chinese enterprises' waiting for exporting, while the rise in the uncertainty will aggravate this effect. This study indicates that it should be the focus of government to actively promote the establishment of bilateral and multilateral free trade zones, to create a stable business environment for enterprises and to reduce the market uncertainty.
Keywords: 330; duration of waiting for exporting; export cutoff productivity; heterogeneity; uncertainty